A PSYCHOLINGUISTIC ANALYSIS OF SPEECH ERRORS MADE BY RACHEL RAY ON TV SHOW - RAKHMAWATI, SULISTIYO AYU (2011)
This research paper is aimed to give a description of speech error phenomena which occur in the Rachel Ray TV Show. This research is to find out the types of speech error, the dominant frequency of speech errors, the sources of speech error and the sources of speech errors in this program. This research is intended to help the readers comprehend speech error phenomenon so that they are careful in producing language. The type of the research is qualitative. The writer downloads the video of Rachel Ray TV Show as the source of data. The data are 120 utterances containing speech errors made by the hostess, Rachel Ray. The researcher analyzes the data based on psycholinguistic approach. From the data analysis, the researcher finds all types of speech error based on the theory of Victoria A. Fromkin. The researcher identifies 8 speech errors uttered by the hostess with the frequencies as follows: shift (16 or 13.33%), exchange (3 or 2.5%), anticipation (3 or 2.5%), perseveration (3 or 2.5%), addition (44 or 36.66%), deletion (21 or 17.5%), substitution (29 or 24.16%), blend (1 or 0.83%). In the mean time, the researcher finds source that cause speech errors. The source is the result of more localized difficulties that speaker has in forming the articulatory program to guide the articulatory muscles in executing speech. It means that speech error is commonly committed by people either native or non-native speakers.